Systemic Management of Relapse Wilms Tumor After Radical Nephrectomy in An Adult Female, A Case Report - PUTRA, IDA BAGUS OKA WIDYA; HARAHAP, EDWARD USFIE; SANTOSO, RACHMAT BUDI (Indonesian Journal of Cancer, 2017)
ABSTRACTWilms tumor (nephroblastoma) is rare in adults. We present a case of 28-year old female with Wilms tumor diagnosed with pre-operative abdominal magnetic resonance imaging, histopathological analysis and immunohistochemistry. She had relapse tumor two years after primary open radical nephrectomy. She was managed with chemotherapy with the ICE regimen (ifosfamide, carboplatin, and etoposide) for six cycles with partial response and excellent functional status. Keywords: ABSTRAKTumor Wilms (nefroblastoma) adalah kasus yang jarang ditemukan pada orang dewasa. Kami melaporkan satu kasus, pasien perempuan, 28 tahun dengan tumor Wilms yang didiagnosis dengan pemeriksaan magnetic resonance imaging pre-operasi, histopatologi, dan imunohistokimia. Pasien tersebut mengalami relaps dua tahun pasca-radikal nefrektomi. Pasien kemudian menjalani kemoterapi dengan regimen ICE (ifosfamid, karboplatin, dan etoposid) selama enam siklus dengan repons parsial dan status fungsional baik.